Good Governance Alokasi Dana Desa (ADD): Peran Perangkat dan Akuntabilitas Publik - Desi Susilawati; Parwoto Parwoto; Puspita Dewi Wulaningrum; Tri Tri Wijayanto (Pusat P2M Politeknik Negeri Batam, 2020)
This research was conducted related to the accountability of the management of the Village Fund Allocation (ADD) 2018 in Village of Tirtomartani, Kalasan District. The research objectives are 1) Measuring the Role of Village Apparatuses in realizing good governance in managing village financial funds, 2) to determine the accountability of ADD management can work effectively for all dimensions, namely Transparency, Accountability and Participation in each process and stage which includes the Planning Phase, Implementation and Reporting 3) to help resolve the problems in the management of ADD so that issues regarding the management of ADD can prove and explain the strategic plans and objectives or the goals that have been planned and established by village government organizations through the meeting mechanism of village development planning. The results of this research that the principle of transparency and participation had been implemented well through the mechanism of consultation and deliberation that involved all elements of village community institutions, indicated by the answers of respondents show 91% answered